Pemanfaatan Teknologi E_Commerce dalam Proses Bisnis pada Era Society 5.0 - Indra Kanedi; Siswanto Siswanto; Yupianti Yupianti; Venny Novita Sari; Bela Oktavia (Jurnal Dehasen Untuk Negeri, 2022)
The development of information technology in the industrial era 4.0 has affected all aspects of life. The growth and development of E-commerce in the community has been felt by all people in all corners of both cities and villages, both among the general public and students. Judging from the many interests in buying and selling online through E-Commerce, it is necessary to prepare competitive human resources through education and training both at school and outside of school. SMK Negeri 2 Bengkulu Tengah is a technology-based vocational school, so it is possible through this school to generate interest for students to understand and learn digital business processes through E-Commerce. The subjects in this service activity were students of SMK Negeri 2 Bengkulu Tengah. The output targets to be achieved in community service activities this time are (1) Students of SMK Negeri 2 Central Bengkulu can understand the use of E-Commerce technology in business processes in the Era Society 5.0, (2) Students of SMK Negeri 2 Bengkulu Tengah are able to describe the influence, readiness and suitability of industry 4.0 with society 5.0, (3) Students of SMK Negeri 2 Bengkulu Tengah can know that through the development and utilization of E-commerce applications in the era of society 5.0 this can improve the economy and trade, because buying and selling transactions can occur anywhere and convenient for customers, reduced transaction costs, information is easy and cheap to obtain as long as within the reach of the internet network.